2022
DOI: 10.1001/jamanetworkopen.2022.33446
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Postbooster Omicron COVID-19 Deaths in England

Abstract: This cohort study of adults in England evaluates the association of sociodemographic and clinical risk factors with death from COVID-19 among individuals who completed primary vaccination and received a messenger RNA (mRNA) booster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…male gender was not found to be significantly connected with disease progression. While in our study and some other studies, 8,43,44 an increased risk was observed in male gender. Several studies have hypothesized that lower testosterone levels in elderly males and males with underlying diseases, as well as hormone differences in inflammatory processes between males and females, could explain these results 7,45 .…”
Section: Discussionsupporting
confidence: 52%
“…male gender was not found to be significantly connected with disease progression. While in our study and some other studies, 8,43,44 an increased risk was observed in male gender. Several studies have hypothesized that lower testosterone levels in elderly males and males with underlying diseases, as well as hormone differences in inflammatory processes between males and females, could explain these results 7,45 .…”
Section: Discussionsupporting
confidence: 52%
“…The odds ratio scores indicate the 60+ age (17.9; 95% CI 16.2–19.8), males (1.3; 95% CI 1.3–1.3), and presence of comorbidities (1.5; 95% CI 1.4–1.5) as potential risk factors. Finally, Nafilyan et al [ 62 ] collected integrated data from the Office for National Statistics Public Health Data Asset (England) to infer the risk factors for COVID-19 death after receiving a booster dose of vaccine during the Omicron wave. The mortality risk was still more strongly correlated with age than with other factors, such as being male and having comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data from well conducted randomized clinical or observational studies providing more specific information on patients who may benefit from therapy are urgently awaited. Specifically, data on the effects of that drugs on acute but also long-term risk reduction of most vulnerable but vaccinated/boostered people, specifically immuno-compromised patients and elderly people with multiple risk factors ( 12 ) would be important to guide and optimize therapy with those anti-viral drugs.…”
mentioning
confidence: 99%